Deep sequencing reveals complex spurious transcription from transiently transfected plasmids - Nejepinska, Jana; Malik, Radek; Moravec, Martin; Svoboda, Petr (PloS one, 2012)
Transient plasmid transfection is a common approach in studies in cultured mammalian cells. To examine behavior of transfected plasmids, we analyzed their transcriptional landscape by deep sequencing. We have found that the entire plasmid sequence is transcribed at different levels. Spurious transcription may have undesirable effects as some plasmids, when co-transfected, inhibited expression of luciferase reporters in a dose-dependent manner. In one case, we attributed this effect to a Kan/Neo resistance cassette, which generated a unique population of edited sense and antisense small RNAs. The unexpected complexity of expression from transiently transfected plasmids underscores the importance of appropriate experimental controls.
Keywords: High-Throughput Nucleotide Sequencing; plazmidy; buněčné linie; RNA, Antisense; Cell Line; Plasmids; průtoková cytometrie; lidé; Humans; vysoce účinné nukleotidové sekvenování; Flow Cytometry; antisense RNA